GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 12486904 species occurrences available in GBIF matching the query: TaxonKey: Lepidoptera HasGeospatialIssue: false Geometry: POLYGON((-39.46 33.65,-39.46 72.10,70.75 72.10,70.75 33.65,-39.46 33.65)). The dataset includes 12486904 records from 840 constituent datasets: 24741 records from Merseyside BioBank (unverified). 5214 records from International Barcode of Life project (iBOL). 22784 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 98478 records from Landesmuseum Kärnten. 5 records from Jordal. 945 records from Alterra (NL) - Entomofauna inventory in peat swamps. 16 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 2546 records from The atlas of butterflies in Kraków. 4611 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 801 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 10078 records from PlutoF platform observations. 80 records from EPA River Biologists data. 299 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 4432 records from Lepidoptera (Observations). 2 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 592367 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 94 records from Local BioBlitz Challenge 2013. 69708 records from HBRG Insects Dataset. 9 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1438 records from Inventario Español de Especies Terrestres (MAGRAMA). 71903 records from Entomology, Natural History Museum, University of Oslo. 926 records from Local Wildlife Site Surveys Berkshire. 16 records from Galls on Beech Trees in Hainich, 2008. 1347 records from ULg_Hexapoda. 4859 records from BioFokus. 74 records from Clare Biological Records Centre dataset. 6 records from Bioblitz 2013 Copenhagen Denmark. 273 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 837 records from Records from the RHS insect reference collection. 7402 records from Helgeland Museum, Lepidoptera. 1 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 7299 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1 records from Plants galls. 1310857 records from Artdata. 310 records from Lepidoptera systematic collection, NTNU University Museum. 1605 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 40 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 25716 records from Butterflies of Ireland. 44 records from SNH Invertebrate Site Condition Monitoring 2013/14: Alvie SSSI. 75 records from The atlas of breeding birds in Małopolska. 347 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 42 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 6 records from Chrysomelidae of the Carpathians. 29 records from NCC Berkshire Chalk Grassland Survey 1985. 4469 records from Données ONF Faune-Flore-Fonge. 1 records from SNH Invertebrate Site Condition Monitoring 2013/14: North Rothiemurchus Pinewood SSSI. 181157 records from Norwegian Biodiversity Information Centre - Other datasets. 3218 records from Invertebrate collection of University of Oulu Zoological Museum. 5 records from Museum of Comparative Zoology, Harvard University. 16 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 526 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 53 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 16 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 15 records from Monitoring data from the federal state Hesse (Germany). 10974 records from iNaturalist Research-grade Observations. 71 records from SNH Invertebrate Site Condition Monitoring 2013/14: Lismore Lochs SSSI. 38439 records from Insects, Outer Hebrides. 149 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 597 records from Dorset SW Pilot species dataset. 2 records from Recent Invertebrates Specimens. 3034 records from Merseyside BioBank Active Naturalists (unverified). 65 records from SNH Invertebrate Site Condition Monitoring 2013/14: Abernethy Forest SSSI. 11342 records from Estonian Museum of Natural History. 4 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 3 records from A revision of the Eudarcia glaseri - species group (Lepidoptera, Meessiidae) with description of two new species from Greece and Crimea. 149 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 39692 records from Estonian University of Life Sciences. 1 records from Essig Museum of Entomology. 1 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 34 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 12 records from Monitoring data from the federal state Saxony (Germany). 1 records from Im Bauerngarten. 3 records from VFD-H: Rheingau: Pferdeweide Loock. 4 records from Seewasen. 23 records from Siegen/ Gymnasium Am Löhrtor. 12 records from Kremmer Luch. 6 records from Feriendorf Ober-Seemen. 4 records from Förderzentrum Schmölln. 9 records from Grenzturm Hohen Neuendorf. 1 records from Lech 2001. 1 records from Fledermaus. 3 records from Feriendorf des Kreises Gedern (Ober-Seemen). 11 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 17 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 1 records from Biotop "Kohlbeke" (Berlin-Marzahn). 2 records from Heidesee / Halle. 8 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 4 records from Fuchsloch (Mohlsdorf/Ostthüringen). 4 records from Naturgrundstück (Eutin). 5 records from Lassentiner Moor (Niepars). 5 records from Kiesgruben Wemb. 1 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 8 records from Truppenübungsplatz Panzerkaserne Böblingen. 6 records from Föhrenried (Fronreute und Baindt). 5 records from Artenvielfalt Kreis Gießen. 2 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 9 records from Regenrückhaltebecken (Zeulenroda). 4 records from Deponie Klausdorf. 14 records from Stadtpark Herzberg (Elster). 4 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 2 records from Zielbach (Töll). 2 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 1 records from Wedeler Au. 1 records from Kabelskebach (Kabelsketal, Saalkreis). 6 records from Steinbruch Mainz-Weisenau. 2 records from Triebesbach (Zeulenroda-Triebes). 2 records from Wiese am Unterbecken. 1 records from verschiedene Kleingewässer um Oldenburg/Holstein. 2 records from "Schwarzes Teich" (Waldpark Radebeul). 11 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 2 records from Örtzemündung (Stedden). 1 records from Hainbachtal in Oelsnitz/V.. 4 records from Wangerooge. 2 records from Umgebung der Grundschule Oderberg. 2 records from Die Wuhle. 13 records from Steinbruch Mainz-Weisenau, 2. Jahr. 10 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 2 records from Wirbach. 7 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 6 records from Paul-Gerhardt-Schule Dassel. 1 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 4 records from Alter Kreidebruch Saßnitz/Rügen. 2 records from Schussenaue bei Berg. 6 records from Rund um das LUGY. 7 records from Ried und Sand - Artenvielfalt durch Beweidung. 2 records from Junge Heide, Radebeul/Dresden. 7 records from Insektenvielfalt Ahe/Weichelsee. 9 records from Schulgarten Hans-Carossa-Oberschule. 3 records from Ludwigshofen. 2 records from Landschaftsschutzgebiet Buchhorst 3. 3 records from Bolzplatz. 1 records from Spielwiese. 1 records from Wassermann. 2 records from Gewässeruntersuchung Grötzinger Baggersee. 1 records from Landschaftsschutzgebiet "Holmer Sandberge". 3 records from Mainufer. 2 records from Rund ums Ökohaus (Würzburg). 7 records from Brander Wald (Stolberg). 7 records from Wiesenbiotop am Wasserturm. 3 records from Balkon (Norderstedt). 8 records from Spießwoogtal / Königsbruch (Fischbach). 5 records from Artenvielfalt im Beckerbruch (Dessau). 6 records from Düne am Ulvenberg (Darmstadt). 27 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 8 records from Ökologischer Weinberg (Guntersblum). 11 records from Schwanseepark (87645 Schwangau). 11 records from Wirbach-Taubental (Bad Blankenburg). 1 records from Trockenrasen bei Dörndorf. 2 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 4 records from Trockenrasen Franzigmark (Halle/Saale). 2 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 2 records from Wiese und Bach beim Unterbecken (Markersbach). 6 records from Garten J. Scherrer (Lachen-Speyerdorf). 3 records from Mauernacker (Wettsaasen). 5 records from Tag der Artenvielfalt BUND Kaiserslautern. 3 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 2 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 13 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 1 records from Artensuche auf den Elbwiesen in Radebeul. 3 records from Umgebung des Spalatin Gymnasium Altenburg. 7 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 2 records from Selztal bei Friesenheim. 2 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 5 records from Naturschutzgebiet Lochbusch-Königswiesen. 8 records from NSG Leist bei Ziegenhain. 9 records from Amtsrain Apolda-Zottelstedt. 4 records from Gieselbachtal Fulda-Harmerz. 3 records from Artenvielfalt auf der Wiese. 1 records from Saalewiesen Naumburg. 6 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 5 records from Flora und Fauna am Mittelrheintal. 20 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 3 records from Schafsweide Seniorenhaus Berghof. 16 records from WildesMoor bei Schwabstedt. 6 records from Binsenwiesen. 5 records from Grillhütte Wettsaasen, Wiese, Hecken. 13 records from Isartal Dingolfing. 3 records from NABU-Auerochsenweide. 1 records from Weidewirtschaft. 6 records from Birkenloh. 10 records from Kochertgraben II. 8 records from Dalbekschlucht. 1 records from VFD-RP: Taunus: Ponykoppel Thurner. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from GE-Brühl. 1 records from Neanderthal. 10 records from Steinbruch Mainz-Weisenau, 3. Jahr. 2 records from Gelände des Schulzentrums am Himmelsbarg. 2 records from VFD-H: Heidenrod: Pferdeweide Mürth. 8 records from Biosphäre Bliesgau. 1 records from Entdeckertour am Muldestausee 1/05. 12 records from Leben im Finkensteiner Moor. 1 records from Wulfsmuehle/Pinnau. 5 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 5 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 4 records from Landschaftspark St.Leonhard-Deisendorf. 1 records from Wiese Niederaula. 2 records from Selz (Ingelheim am Rhein). 4 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 2 records from Schulgelände Kranich-Gymnasium (Salzgitter). 2 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 3 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 7 records from Kinderbauernhof Pinke-Panke. 1 records from Stausee Weiditz. 2 records from LSG "Großes Bruch". 14 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 7 records from Römertal (Steinpleis). 3 records from Sternwiese Mülheim-Broich. 32 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 1 records from Naturerfahrung. 2 records from Steinbachtal (Würzburg). 1 records from Schulhof A.-Lindgren-Schule (Elmshorn). 1 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 4 records from Garten in Schmölln. 1 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 5 records from Plöwener Wald. 1 records from Dörnberg. 3 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 1 records from Regenwasserabfangbecken. 4 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 5 records from Schafheide im Böblinger Wald. 1 records from Regenrückhaltebecken Bad Bevensen. 1 records from Naturschutzgebiet Kochertgraben. 7 records from Streuobstwiese Haus Zeitz. 1 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 5 records from Hoher Stein Kallenhardt. 5 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 2 records from Schulgarten-St.-Georg-Gymnasium. 1 records from Estetal (Buxtehude). 6 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 1 records from Zwickau- Schwanenteich. 2 records from Schulgelände Lise Meitner Realschule (Paderborn). 107 records from Sudeniederung (Amt Neuhaus). 2 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 3 records from Olympiapark (München). 3 records from Lahnufer in Villmar. 5 records from Kaisertal. 9 records from Heider Bergsee (Brühl). 1 records from Wiese hinter der Schule (Darmstadt). 2 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 3 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 2 records from Insekten. 20 records from IBF Monitoring of Plant Galls. 1 records from Warnowufer Groß Klein. 1 records from Feuchtwiese. 2 records from Krittenhorster Wald (Ostkilver). 2 records from LBV-Kindergruppen Markt Tussenhausen. 1 records from Wattenmeer-Safari (Wurster Watt). 1 records from Kleinstbiotop mit Schulteich/Weißwasser. 1 records from Sächsische Schweiz (Pfaffenstein). 1 records from Nachtaktiv im Ökogarten (Bad Waldsee). 1 records from Privatteich(St.Leon). 1 records from Urwald 2 (Bad Waldsee). 1 records from Tiere. 4 records from Landschaftsschutzgebiet Buchhorst 4. 2 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 3 records from Stadtrandlandschaft Apolda-Nord. 2 records from Rotes Steigle (Panzerübungplatz Böblingen). 4 records from Waldi-Weiher. 1 records from Hildener Heide - Spörkelnbruch (Haan). 3 records from Tiere und Pflanzen am Pfannenbach. 52 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 103 records from FFH-Gebiet "Calwer Heckengäu". 2 records from Landschaftsschutzgebiet Schmutterwald. 2 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 1 records from Tag der Artenvielfalt am Bruckenwasen. 110 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 60 records from Bannwald Burghauser Forst. 7 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 6 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 16 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from Fürstenberger Ralley Teil 3. 2 records from Müritz-Nationalpark. 9 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 2 records from Kühnauer Aue und Kühnauer See. 8 records from Naturschutzstation Weinberghaus (Dessau). 21 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 31 records from Pöhlberg bei Annaberg. 3 records from Kaniswall/ Gosener Wiesen an der Spree. 3 records from Expedition "Schulgelände". 67 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 3 records from Haarbach Höfe. 3 records from Schulzentrum "Parc Hosingen". 4 records from LK 11 im Mönchspark. 3 records from Schulwald Grundschule Brügge. 11 records from Bernhardsthal. 26 records from Weinberg Reichersdorf. 3 records from Schulwald Marksuhl. 1395 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 1 records from BIRDRACE Griffin Wood Warblers. 25 records from Naturschutzgebiet Börstig bei Hallstadt. 18 records from Tag der Artenvielfalt in Heidelberg. 4 records from Tongrube bei Hettstedt. 21 records from FFH-Gebiet Klosterwasser/Burkau. 2 records from Gronau - auf der Suche nach dem Neunauge. 2 records from Langes Tannen(LMS), Klasse 5d. 2 records from Liether Park 2 (LMS), Klasse 6c. 23 records from Schatzinsel Wangerooge. 2 records from Lustbach-Umland. 1 records from Königsdorfer Wald. 1 records from VFD-HH/SH: Pferdweide Lammert. 5 records from Owere Fiddel. 6 records from NSG Forst Zinna-Jüterbog-Keilberg. 5 records from Hettstadt Gehäge. 18 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 13 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 1 records from Tornoer Teich. 2 records from Streuobstwiese Stedar. 6 records from Liether Kalkgrube. 1 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 5 records from Schulgarten der Volksschule. 6 records from Sürther Aue. 3 records from Aachtobel. 21 records from Bodenteicher Seewiesen. 9 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 2 records from Wälder im Hainbachtal. 4 records from Steinbruch Kronungen. 4 records from Ober-Olmer Wald. 1 records from Rund um den Hainbergsee. 2 records from "Ahrschleife bei Altenahr". 5 records from Pflanzen und Tiere im Burgwald. 2 records from Wir erkunden die Hofau, Klasse 5c. 1 records from Waldwiese. 3 records from Von der Nutzung zur Natur. 1 records from Liether Park 1 (LMS), Klasse 5b. 1 records from Schulgarten Waldorfschule Hassfurt. 1 records from Unter hellen Zinnen und finsteren Grotten. 1 records from FFH-Gebiet Paartal. 3 records from Schulgelände Grolland. 2 records from Schulgarten Janusz-Korczak-Realschule. 3 records from Düpenauwiesen. 3 records from Wahner Heide LK 12 Biologie. 4 records from Aktion der Klasse H2 in Simmelsberg. 9 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 1 records from VFD HH/SH "Pferdeweide Lemsahl". 1 records from Was lebt in der Brutzwiese?. 1 records from Reusaer Wald. 3 records from Rechts des Inn Höhe Hofau Rosenheim. 2 records from Feuchtwiese Grüne Mitte, Klasse 5a. 1 records from Teich im Wald zwischen Böblingen und Schönaich. 3 records from Nachtinsekten am Muldenufer. 1 records from Höhle am Neuweg / Sächsische Schweiz. 7 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 101 records from Biodiversity records from Ireland - general. 4 records from Illinois Natural History Survey Insect Collection. 254 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from Polish seed gene bank – historical passport data of accessions. 254979 records from naturgucker. 806 records from flower visitor interactions 2008. 14 records from SNH Invertebrate Site Condition Monitoring 2013/14: Black Wood of Rannoch SSSI. 5 records from Vertebrats d'Andorra. 4200 records from Entomological collections, UiB. 135326 records from Natural History Museum Rotterdam (NL) - Lepidoptera observations. 1 records from English Nature Oxfordshire Chalk Grassland Survey. 16702 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 191314 records from The Distribution Atlas of Butterflies in Poland. 3095 records from National Trust - Hatfield Forest species data held by The National Trust.. 2303 records from Lepidoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 60 records from Freiburger GEO-Tag der Artenvielfalt. 3 records from Sandloch - Höhle. 190 records from Biosphärenpark Wienerwald - Pfaffstätten. 29 records from Kühmark bei Wetzlar. 51 records from Eschlberg Thalhausen. 63 records from GEO-Hauptveranstaltung in "Wildtierland". 25 records from Sahrbachtal Kreis Ahrweiler. 3 records from Schulgelände des Schulzentrums am Himmelsbarg. 3 records from Baggerseen bei Krauchenwies. 1 records from Schriesheimer Steinbruch. 1 records from Artenvielfalt in der Kinderakademie im RFZ. 10 records from Mangfalltal. 1 records from Wälder und Seen rund um den Mühlenberg. 6 records from GEO-Tag am Hohlen Stein. 5 records from LBV 100 - Artenvielfalt am Rothsee. 3 records from Naturpark Kottenforst-Ville 18.6.09. 4 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 109 records from Bayerische Donau - Leipheim. 66 records from Koleopterologen am Bausenberg. 146 records from Artenvielfalt im Rhein-Neckar-Raum. 15 records from Schatzinsel Norderney. 62 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 11 records from Biotope in Rheine - Aktion 350. 3 records from Artenvielfalt am "Grünen Band" bei Coburg: 20 Jahre Wiedervereinigung. 5 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 6 records from Dornwanger Moos. 4 records from Die Teiche im Britzer Garten. 12 records from Butterberg, Dardesheim. 1 records from Nationalpark Jasmund. 10 records from Bulau. 5 records from Luderbusch. 3 records from Werl macht sich auf die Suche. 6 records from Rur. 1 records from Parkuntersuchung Weißer See. 8 records from Feuchtbiotop Weidenkaule. 12 records from Wälder bei Nordkirchen. 1354 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 2 records from BB-Biodiversität b. 1 records from Projekt Dellbrücker Heide. 1 records from Rund um die Sausenburg. 8321 records from Artròpodes d'Andorra. 13 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 14 records from Bayerische Donau - Blindheim Donaubrücke. 2 records from Streuobstwiese Stedar 2008. 2 records from Schloss Fasanerie Eichenzell. 1 records from Donauinsel des BN bei Entau. 10 records from Streuobstwiese Stedar 2009. 1 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 5 records from Liether Park (LMS), 5a. 15 records from Schiller Gymnasium Hof 10b. 68 records from Schieferbrüche. 1 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 3 records from Reifrocknarzissenwiese Löcknitz. 2 records from Schulhofuntersuchung Thomas-Mann-OS. 2 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 6 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 7 records from Listhof und Umgebung. 1 records from Naturpark Kottenforst-Ville 16.6.09. 5 records from Raus in die Natur. 4 records from Rund ums Schulgelände. 3 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 1 records from Bayerische Donau - Neu Ulm. 8 records from Exkursion Ebertsheimer/Grünstädter Berg. 13 records from Binsenwiesen im Bizzenbachtal. 2 records from Oberes Schindelbachtal. 4 records from Leben in den Elbwiesen. 1 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 5 records from Wiesen in der Grünen Mitte. 5 records from Naturschutzgebiet Lüneburger Heide. 3 records from Dalbek-Schlucht. 4 records from Bonner Schülerinnen am Rodder Maar. 6 records from MfN - Fossil invertebrates Ia. 2 records from MfN - Trace fossils. 1 records from MfN - Fossil plants (Cenophytic). 1 records from Mammal Collection. 17732 records from Natural History Museum Maastricht (NL) - Entomological Collection. 25979 records from Insekten Sachsen. 705940 records from Vlinderdatabank - Butterflies in Flanders and the Brussels Capital Region, Belgium. 1 records from Rådgivende Biologer. 113 records from BioBlitz Barcelona 2010-14. 2 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 122 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 77 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 2 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 84 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 1 records from Bayerische Donau - Riedlingen. 3 records from Bayerische Donau - Tapfheim. 7 records from Artenvielfalt rund um die Dalbek-Schule. 7 records from "Schule am Inselsee" Güstrow. 4 records from Familientag am Schorberg. 10 records from Aktionstag Wiese am Vogelhammerkopf. 1 records from 2. Aspacher GEO-Tag der Artenvielfalt. 8 records from Fliegenhaupt Marksuhl. 389 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 1 records from Fluss - Vielfalt. 2 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 1 records from Grundschüler erkunden Schulumgebung. 13 records from Grünes Germersheim. 1 records from Kindervilla Aussengelände/ Hiltroper Park. 6 records from Ober-Olmer Wald 09. 3 records from Ortsrand Zandershagen. 4 records from Projekt Wahner Heide. 2 records from Schulgarten Am Hafen. 5 records from Schulwald Sprendlingen. 1 records from Steinbruch Mainz-Weisenau, 4.Jahr. 2 records from Sukzession Industriebrache. 10 records from Wasser-Lernort Nettemündung. 1 records from Wuhle - Brücke / B1. 5 records from Insect Collection of Yokosuka City Museum. 12 records from IZIKO South Africa Museum Collection (1800-2013). 113546 records from Data on moths from automatically operating light traps in Denmark. 95238 records from Tiroler Landesmuseum Ferdinandeum. 1 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 64541 records from Norwegian Lepidoptera working group. 36 records from Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 167181 records from BRERC species records recorded over 15 years ago. 18393 records from SysTax - Zoological Collections. 1948 records from Naturhistorisches Museum Mainz, Zoological Collection. 162734 records from Natural History Museum (London) Collection Specimens. 2455 records from Bumblebees, cuckoobees and butterflies in southern Poland. 198205 records from Atlas Survey of the Butterflies of Denmark. 76 records from New findings of the butterfly Phengaris teleius at the border between Hungary and Serbia (Lepidoptera: Lycaenidae). 10 records from UAM Insect Collection (Arctos). 16929 records from Lepidoptera (Specimens NRM). 2674 records from Ireland's BioBlitz. 17 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 35 records from IG TUT paleontology. 2 records from Tartu University, palaeontology collections. 11727 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 2 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 203 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 37 records from Edaphobase. 531415 records from Swiss National Butterflies Databank. 209 records from Laboratorio de Entomología y Control de Plagas del Instituto Cavanilles de Biodiversidad y Biología Evolutiva de la Universidad de Valencia: ENV. 2225 records from Database on Forest Disturbances in Europe. 1 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 283 records from SNH Invertebrate Site Condition Monitoring 2013/14: Ben Lomond SSSI. 102 records from Paleobiology Database. 10 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 8739 records from Bryotropha (Lepidoptera: Gelechiidae) in Western Palaearctic. 2861 records from ConDidact Citizen Science Surveys - Spiders 2004 Butterflies 2005. 2409 records from European Lepidoptera Observations by Donald Hobern. 139693 records from Lepidoptera collection of Hannu Saarenmaa. 2 records from Invertebrate Paleontology Division, Yale Peabody Museum. 20 records from GEO Biodiversity Day. 908751 records from Biologiezentrum Linz. 1 records from The Erysiphales Collection at the Botanische Staatssammlung München. 140 records from Arthropod fauna in christmas tree plantations. 112026 records from inatura - Erlebnis Naturschau Dornbirn. 2 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 5177 records from European Moth Nights. 15124 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 7787 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 754266 records from Bugbase, Lepidopterological Society. 2537 records from Staffordshire Ecological Record - SER Site-based Surveys. 120195 records from Biodiversitätsdatenbank des Landes Salzburg. 47 records from English Nature Berkshire SSSI Records. 6241 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 53 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 54 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 57 records from BÜG. 31 records from LaBoOb02. 3 records from Pfrimmersbachtal. 6 records from Klutensee. 8 records from Überall ist Wunderland. 6 records from DJH. 6 records from Am Moosangerweg. 1 records from Frau Voss. 264 records from Danielsberg (Mölltal, Kärnten). 14 records from Streuobstwiese RSG (Cham). 26 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1 records from FFH-Gebiet Ahrbachtal. 10 records from Botanischer Garten (Saarbrücken). 25 records from Trockenhang Greinhartsberg Edelfingen. 153 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 13 records from Hamberger Brücke / Würmtal (Pforzheim). 10 records from Artenvielfalt auf den Elbwiesen (Dessau). 5 records from Schulgelände (Wetter). 7 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Sandhofen. 18 records from Schlichemquelle (Tieringen/Meßstetten). 12 records from Mooswald (Freiburg). 83 records from Gemeinde Sursee. 49 records from Gewann Krampf (Heilbronn). 17 records from Naturschutzstation Schmidsfelden. 4 records from Landschaftspflegehof (Berlin). 48 records from Naturschutzgebiet Bausenberg. 9 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 1 records from Altholzparzelle Eilenriede Hannover. 2 records from Schulhof Bühlschule Giengen. 68 records from Schlern - (Bozen). 408 records from GEO Hauptveranstaltung Tirol (Innsbruck). 12 records from Schule Sulzbach (Oberegg). 17 records from Zukünftiges NSG Höftland/Bockholmwik. 75 records from Königstetten. 3 records from Frauenholz (Holzmaden). 14 records from Freiburger Tag der Artenvielfalt. 2 records from Erzental (Oberotterbach). 8 records from Langes Tannen (Uetersen). 66 records from Gelände des IVL (Zeckern). 16 records from Stausee (Oberdigisheim/Meßstetten). 18 records from Naturschutzgebiet Bausenberg (Niederzissen). 62 records from Erlengraben/Lipp-Tal (Östringen). 4 records from Wald und Wiese am Buchwald. 4 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 21 records from NSG Karwendel. 16 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 43 records from Neckartalsüdhang (Horb). 9 records from Umgebung der Gesamtschule Hamburg-Winterhude. 3 records from Langes Tannen. 3 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 7 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 1 records from Schulgarten Huttenheim (Philippsburg/Baden). 1 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 2 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 14 records from Philosophenwald und Wieseckaue in Gießen. 5 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 1 records from Artenvielfalt auf Restbauernhof. 7 records from Wiese und Weide am Waldrand von Gusterath. 9 records from Blumenrather Heide / Virneburg. 78 records from Cuxhavener Küstenheiden. 3 records from Umgebung von Schorndorf. 298 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 11 records from Danisco-Wiese. 3 records from nazza. 1 records from Birkenpilz. 6 records from katzenbuckel. 14 records from Promberg1. 7 records from Biologische Station im Kreis Wesel. 238 records from GEO-Hauptveranstaltung (Insel Vilm). 28 records from GEO-Hauptveranstaltung (Duisburg). 2 records from Wanderweg am Windebyer Noor (bei Eckernförde). 131 records from BUND - Dassower See (Lübeck/Dassow). 19 records from Wildes Bremer Leben im Park. 3 records from Entdeckertour am Muldestausee. 5 records from Schulhof (Bad Waldsee). 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 27 records from Unser Schulgelände. 8 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 2 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 2 records from Nottekanal, Klasse 7 - 10. 8 records from Luch Niederlehme, Schüler der Klasse 7. 4 records from Stadtbiotop Ulrichteich. 186 records from Pilstingermoos. 129 records from Artenfülle um das Schalkenmehrener Maar. 11 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 30 records from Riedensee. 6 records from Streuobstwiese Kattenhund (Schleswig). 7 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 184 records from Gurgltal (Tarrenz). 3 records from Überschwemmungsgebiet der Wied. 23 records from 20 Jahre Naturschutzgebiet Dreienberg. 5 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 60 records from Heinersdorfer Sumpfwiese. 8 records from Schaalbach. 2 records from schulgarten. 14 records from NSG Nollig. 1 records from Pottundkopp. 15 records from Knechtweide (Kohlfurth). 7 records from Wald am Schloss Wittgenstein Bad Laasphe. 3 records from Industriegebiet (Kempen). 6 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 4 records from Ökostation (Freiburg). 8 records from Bergbaufolgelandschaft am Muldestausee. 72 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 5 records from Regionalpark(Hattersheim). 1 records from Langes Tannen in Uetersen. 16 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 8 records from Schulhof Goethe-Gymnasium (Emmendingen). 4 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 15 records from Kiesbagger (Mittelhausen). 12 records from Biotop Binsenwiesen (Wehrheim/Taunus). 8 records from NSG Berschau - Auengebiet (Neustadt / Wied). 6 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 3 records from Schulumfeld Albert-Einstein-Gymnasium (Sankt Augustin). 15 records from Gemeindegebiet Weikendorf (Marchfeld). 4 records from Umgebung der Gesamtschule Winterhude (Hamburg). 2 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 3 records from Natur aus zweiter Hand am Muldestausee. 14 records from Schulgelände Schule auf der Aue, Münster. 5 records from "Tre Pini" (Montebelluna, Italien). 6 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 40 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 22 records from Schloß Türnich (Kerpen). 7 records from Quarrendorfer Landschaftsschutzgebiet. 15 records from Faberpark (Nürnberg/Stein). 1 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 31 records from Streuobstwiese Kugelberg (Ulm). 9 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 4 records from Südwestlich der Parkwiesen. 3 records from Wismar Bucht coast-watching. 2 records from Schulprojekt (Bremen). 2 records from Fuldaaue (Stadtgebiet Fulda). 13 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 6 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 11 records from Bergkamen- Bergehalde Großes Holz. 1 records from Stadt Königs Wusterhausen. 4 records from Stadtpark Sulzbach-Rosenberg. 4 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 1 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 6 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 1 records from Schulhof und Anlagensee in Nellingen. 2 records from Tiergarten Straubing. 25 records from Vorderer Tiergarten (Dessau). 3 records from Bizzenbachtal (Wehrheim/Taunus). 1 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 2 records from Werremündung im Schwarzatal. 1 records from Naturschutzgebiet Müchelholz (Mücheln). 12 records from arthropods on Plantago lanceolata. 49 records from Eppingen und Umgebung. 6 records from Steinbruch Haas Stuttgart-Münster. 11 records from Weidenhüttendorf an der Würm (München). 18 records from renaturierter Main (Kemmern bei Bamberg). 1 records from Unterbrucker Weiher. 46 records from 3. Tag der Artenvielfalt Hockenheim. 6 records from Prophetensee Quickborn. 19 records from Kühnauer See (Dessau). 7 records from Halberg bei Neumorschen. 3 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 4 records from Hintere Halde. 1 records from Steinbruch Pluwig. 4 records from Lebensraum Stadt und Park. 6 records from Schussenaue (Weingarten). 7 records from Wupperaue bei Kemna (Wuppertal). 16 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 2 records from An der Ohm, (Wettsaasen). 4 records from Freiheitsring (Frechen). 2 records from Spandau HBO. 1 records from Dreilinden Gymnasium-Schulgelände. 5 records from Maschwiesen Laatzen. 4 records from Himmelmoor. 11 records from Altenburg bei Bamberg. 61 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 53 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 10 records from Naturerlebnisraum Koppelsberg. 6 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 29 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from Innenstadt Göttingen - Natur Zuhause. 10 records from Mißmahlsche Anlage. 11 records from Teich Berlin Wuhlheide. 4 records from Artenvielfalt im Umfeld der Burgwegschule. 21 records from Naturgarten Langenholtensen. 6 records from VSN-Wiese. 4 records from Tag der Artenvielfalt. 1 records from Artenvielfalt auf dem Schulgelände. 22 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1 records from Schulgelände SGD/Viersen. 13 records from Unna-Mühlhausen, Wiesen. 1231 records from Natural History Museum, University of Tartu. 3 records from English Nature Grassland Survey 1995. 51 records from Homoptera. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 108 records from Perchtoldsdorfer Heide. 1 records from Naturpark Drömling. 3 records from Schwanheimer Wald. 27 records from Freiburger Netzwerk Artenvielfalt. 69 records from Rössewiesen am Krumbholz. 26 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 59 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 6 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 3 records from Berkel. 8 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 14 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 2 records from NSG Haunestausee, Hauneteiche. 1 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 5 records from Ostfriesland. 2 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 10 records from Biosphärenreservat Münsinger Alb. 9 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from Kaulsdorf. 4 records from Auenwiesen und Trockenrasen. 40 records from Lustadter Wald .. 1 records from Waldwandel in Monschau-Mützenich-Boverei. 8 records from Kohlstattbrunnental. 2 records from Klostergarten St Luzen. 11 records from Naturnahes Tal in Siena. 17026 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1527 records from EDIT - ATBI in Gemer area (Slovakia). 561 records from EDIT - ATBI in Borjomi/Kharagauli (Georgia). 7 records from ELM paleontology. 10580 records from DOF. 26158 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 6281 records from Invertebrate collection of Jyväskylä University Museum. 68 records from Artenvielfalt am Schlern. 3 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 314198 records from Biological and palaeontological collection and observation data MNHNL. 239 records from Entomology Division, Yale Peabody Museum. 5 records from Tag der Artenvielfalt im Taubental. 1 records from Collection Polychaeta SMF. 6504 records from DOF 2001-2006. 2653 records from Butterflies. 1 records from River macroinvertebrate data for 2005 and 2006. 886 records from English Nature Oxfordshire Invertebrate Surveys. 208 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 1 records from Invertebrates (except insects), Outer Hebrides. 1 records from A systematic revision of the genus Gnophopsodos Wehrli, 1945, with description of two new species (Lepidoptera: Geometridae). 436 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 734 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 315 records from Wetland Inventory (NV). 5 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 92344 records from Butterflies - Irish Butterfly Monitoring Scheme. 1 records from SNH Invertebrate Site Condition Monitoring 2013/14: Flanders Moss SSSI. 4 records from Limnodata. 5 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 43 records from National Trust - Sutton Hoo species data held by The National Trust.. 3404 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 2360656 records from Finnish Entomological Database: Lepidoptera. 1 records from National System of Protected Areas in Poland - Plants. 59976 records from ArtenFinder. 4 records from Snow Entomological Museum Collection. 52 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 654 records from National Trust - Ickworth species data held by The National Trust.. 9243 records from Geographically tagged INSDC sequences. 14 records from 2000-2003 RBWM WHS Surveys. 423 records from flower visitor interactions 2007 Schwäbische Alb. 217898 records from Norwegian Species Observation Service. 4 records from Casual records for Scottish Wildlife Trust reserves - Unassessed data. 48 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 581 records from Merseyside BioBank Active Naturalists (verified). 12 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 23 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 123 records from SNH Invertebrate Site Condition Monitoring 2013/14: River Spey - Insh Marshes SSSI. 13902 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 259409 records from Staffordshire Ecological Record - SER Species-based Surveys. 15 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 1 records from Royal Botanic Garden Edinburgh Herbarium (E). 19 records from Botany (UPS). 60 records from SNH Invertebrate Site Condition Monitoring 2013/14: Crathie Wood SSSI. 1 records from MUST, Insecta. 8331 records from LNHG Biological Records Dataset. 1 records from English Nature Berkshire Staff Surveys 1990's. 6974 records from Merseyside BioBank (verified). 2 records from Yorkshire Naturalists Union Marine and Coastal Section Records. 2 records from Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae). 1490 records from Estonian Nature Observations Database. 978 records from Ghent University - Zoology Museum - Insect collection. 40946 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 240 records from Entomological specimens of Museum fuer Naturkunde und Vorgeschichte Dessau. 1 records from Vascular plant herbarium, Tromsø Museum. 286 records from Butterflies 2008. 3 records from Vascular plant herbarium, NTNU University Museum. 4470 records from Données ONF Faune-Flore-FOnge. 889 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 91 records from National System of Protected Areas in Poland - Animals. 62992 records from Natural History Museum Rotterdam (NL) - Insecta collection. 2 records from Ecofact. 1 records from Die Milbenfauna der Nordseeinsel Wangerooge. 14 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 18 records from Herbivorie_Pflanzenebene_2008. 243 records from Australian Museum provider for OZCAM. 1 records from Miscellaneous Vascular Plants. 2849 records from Biodiversity Now / Nature Check (Biodiversitet Nu / NaturTjek). 9 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 6 records from Herbarium of University of Białystok - Vascular Plants. 108 records from National Trust - Heigham Holmes species data held by The National Trust. 24 records from BioFresh Pond Data. 49 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 3484 records from Lepidoptera collection of NW Europe. 176 records from Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 10 records from Vascular Plant Herbarium, Oslo (O). 1659 records from Local Wildlife Site Surveys Oxfordshire. 492 records from Anymals+plants - Citizen Science Data. 1801081 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 180 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 12010 records from Arthropod collection, Tromsø Museum. 7124 records from National Trust for Scotland Species Records. 1952 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 11614 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 6165 records from Data collected on scitizen science web portal www.ornitho.cat. 3 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 37476 records from Insects from light trap (1992–2009), rooftop Zoological Museum, Copenhagen. 1 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 83 records from English Nature and NCC Oxfordshire Surveys. 457235 records from BRERC species records within last 15 years. 54 records from Species observations during citizen science expeditions. 18 records from NCC Berkshire Grassland Survey 1984-1987. 653 records from HBRG P.F. Entwistle Insects Dataset. 6 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 4772 records from Butterflies of County Waterford. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences